The Effect of Quality of Work Life on Employees' Organizational Commitment With Interpersonal Communication as A Moderating Variable on Health Officers at The Namorambe Public Health Center - Dinda Saranisah Putri; Hasanuddin Hasanuddin; Kaiman Turnip (Dinasti International Journal of Education Management and Social Science, 2025)
Organizational Commitment is a psychological state that makes employees believe they will always be in the organization in order to achieve performance targets and want to always be with the organization forever. Quality of work life is a form of perception about the atmosphere, experience, job satisfaction and opportunities for growth and development in the organization. Interpersonal communication is the delivery of a message by one person and the reception of the message by another person or small group of people, with varying impact and with the opportunity to provide immediate feedback. The aim of the research is to examine the influence of quality of work life on organizational commitment, the influence of quality of work life on interpersonal communication, the influence of interpersonal communication on organizational commitment and the influence of quality of work life on organizational commitment with interpersonal communication as a moderating variable. This research uses quantitative methods. In this research, the sampling technique used was total sampling. The results of this research show that there is an influence between quality of work life and organizational commitment with a t-statistic value of 2.112 > 1.96 and/or a p-value of 0.035 < 0.05 (hypothesis accepted). There is an influence between quality of work life and interpersonal communication with a t-statistic value of 35.605 > 1.96 and/or a p-value of 0.000 < 0.05 (hypothesis accepted). Furthermore, there is an influence between interpersonal communication and organizational commitment with a t-statistic value of 35.061 > 1.96 and/or a p-value of 0.000 < 0.05 (hypothesis accepted). And for the final results it is explained that there is no influence between quality of work life on organizational commitment and interpersonal communication as a moderating variable with a t-statistic value of 0.683 < 1.96 and/or a p-value of 0.495 > 0.05 (hypothesis is rejected)